TEACHING SPEAKING NARRATIVE THROUGH ANIMATED FABLE VIDEOS TO THE EIGHTH GRADERS OF MTS-ANNAMIRAH, BANGKALAN, MADURA (RETAIN, 2014)
TEACHING SPEAKING NARRATIVE THROUGH ANIMATED FABLE VIDEOS TO THE EIGHTH GRADERS OF MTS-ANNAMIRAH, BANGKALAN, MADURA ABDUS SUBUR English Education Department, Language and Art Faculty, Surabaya State University. abdus.chaidar@gmail.com Dra. Hj. Syukriah Abdullah English Education Department, Language and Art Faculty, Surabaya State University. Abstract The importance of speaking English is often set aside and is considered being the most difficult skillS among the others. Therefore, it is so crucial for the English teachers to keep trying to find ways or creativities to teach this skill. One of the easy ways is to use video in teaching students to speak English as it can give the real model of the target language. This study is an attempt to answer the three research questions -dealing with the implementation of video in teaching speaking: 1. How is the implementation of teaching speaking narrative through animated fable videos? 2. How are the students’ speaking narrative after the implementation of animated fable videos? 3. How are the students’ responses in teaching speaking narrative text through fable videos? Since this study was descriptive qualitative study, the writer would describe and analyze the existing phenomena during the study. In this case, the study was done in three meetings which took twenty seven students of the eighth grader of junior high school as the subject of the study. The place of the study was at Mts Annamirah, Bangkalan, Madura. There were three kinds of instruments used in this study, they were observation checklist, students’ speaking tasks, and questionnaire. From the findings, the writer noticed that the implementation of video mostly had the same activities although it was done in three meetings. The notes were about the analysis of teacher’s activity, students’ activity, teaching and learning process, material, and media used. At this point, the first viewing was a video entitled “Kaalu, The Thirsty Crow”, the second viewing was “Dove and The Ant”, and the last viewing was “The Foolish Fox”. In addition, the implementation of teaching speaking narrative through animated fable video helped students’ mastery on narrative text in retelling the story. This could be seen in the students’ speaking progress in each term of speaking components. Meanwhile, the result of students’ responses showed that the students were mostly interested in video viewing and agreed that video was helpful in getting the ideas to speak. Keywords: speaking narrative, animated fable videos INTRODUCTION The era of globalization and rapid advancement of technology will definitely give a great impact tothe English methodologies. Teachers will easily modify the teaching media using Internet access and computer to enhance the students learning, as it is stated by Warschauer (1998), a determinist position associates the mere presence of computers with successful language learning. In other words, technology has an extraordinary effect on learning, and simply including it will determine a more positive outcome for any activity. Learning English has also become the most dominant wayto support careers and as one of the important subjectsto pass the national exams. Studentsare obliged to master English.To master academicEnglish means to master the language skills such aslistening, writing, reading, and speaking, and the languagecomponents are Grammar, vocabulary, pronunciation, and spelling.Apart fromthe language skills, speaking ability howeverisoften set aside and considered as the most difficult skill to learn. (Brown and Yule (1983) state that learning to talk in the foreign language is often considered being one of the most difficult aspects of language learning for the teacher to help the students with. In order to speak one language like English, one should always practice it whenever and wherever possible."We learn to speak by speaking" (Swain1985).The more you practise the more you will improve your own oral skills as well as help your students. On the other hand, (Chaney, 1998, p. 13) also states,” Speaking is "the process of building and sharing meaning through the use of verbal and non-verbal symbols, in a variety of contexts". Teachers,here therefore are challenged to promote various teaching techniques in teaching speaking skill as the variety of teaching techniques that will help learners to get higher motivation to learn to speak. William and Burden 1997:111)stated thatmotivation is the most powerful influences on learning. One of the teaching techniques that can motivate in teaching speaking is the use of video. Rice(1993)saysthat video has so muchto offer, as it Heimei (1997) also states that students love video because video presentation is interesting, challenging, and stimulating to watch.Students will enable to have authentic experience in controlled environment and contextualizing language naturally byshowing real life into the classroom.Sherman (2003:3) also claims that there is a special thrill in being able to understand and enjoy the real thing in video. Moreover, video provides a clear short term achievable aim for students and much easier to carry out their own conversation. Based on the ideas that videos can be carried outinto many kinds of students’ need to master English like speaking ability in which mostly students find trouble with, the writer would like to conduct a study dealing with teachingspeaking narrativethrough animated fable videosto the students ofMTs Annamirah, Bangkalan, Madura, with an expectation to help the students to get better ability to tell narrative stories as well as to get them have deeper comprehension on narrative text types in which they often just find such stories in written texts. Itis as well hoped in order to be a kind of new atmosphere for both the teacher and students in orderto make English learning and teaching activities become more exciting and to get the target language. METHOD The aim of the study is to find out the method used by the writer in conducting the study and the subject studied. They are research design, subject of the study, research instrument, data collection techniques, and data analysis. In conducting the research, research design plays an important role in obtaining the data, related to the research questions stated on chapter one: 1) how is the implementation of teaching speaking narrative through animated fablevideos? 2) how well are the students’ speaking narrative after the implementation of animatedfable videos? 3) how are the students’ responses in teaching speaking narrative throughanimatedfable videos? The writer used descriptive qualitative study as the research design in which focuses on understanding and meaning through verbal narratives and observations rather than through numbers (McMillan, 1992:9). Theresult of the research, therefore is in the form of description and interpretation of some phenomena that exist during the research. The study conductedat MTs Annamirah, Bangkalan, Madura, VIII-B class with the total number of27 students, 14 boys and 13girls, in the 2nd semester, academic year 2013 - 2014. The selected class is based on theteacher’s consideration that the English ability of the students is on the average, at the same time it is expected to improve the students’ speaking ability. There were three instruments used by the researcher in his study: observation checklist, test, and questionnaire. Observation checklist was used to find out the phenomena dealing with the implementation of animated fable video in teaching speaking narrative. The phenomena observed were including the points about the teacher’s activity, the students’ activity, teaching and learning process, material, and media. Speaking task was a method to measure the students’ abilities on their speaking narrative, after the implementation of animated fable video as well as is expected to help students improve their speaking in telling narrative stories which included the students’grammar, vocabulary, fluency, pronunciationand comprehension. Questionnaire was used to find out the students’ responses to teaching speaking narrative through animated fable videos. The questionnaire is a closed – end questionnaire which is expected the respondent to answer fast and to choose the possible optionsprovided. To get the data for this study, the researcher usedsome techniques; the data was collected through non-participant observation, that was the writer only observed the process of teaching and learning in order for the teaching and learning activities went naturallyby using observation checklist. On the other hand, the writer not only observed but also recorded the whole teaching and learning activitiesandphenomena, when the animated fable video was implemented as the media in teaching speaking narrative. To obtain the related data to teaching speaking narrative through animated fable videos, the speaking task of the students was taken to find out theirspeaking ability, since the implementation of animated fable videos and was expected to them make up theirspeaking narrative based on its generic structure and language feature. For the students’ speaking, there were three short animated fable video implementations with different topics which was done in three meeting and every meetingthey were asked to speak narrative while and after watching the videos. In addition, the students’ responses towards the implementation ofteaching speaking narrativethrough animated fable videos were also regarded very important.Thewriter thereforespread out questionnaires to know how far students’ interest and difficulties are.There were seventeen questions in the questionnaire and they were in the form of multiple choices and were given in the last meeting of the implementation of video since it was considered efficient.The indicators in the questionnaires are: Question 1-2 dealt with students’ opinion about speaking. Question 3-5 dealt with students’ opinion about the implementation of speaking narrative through animated videos. Question 6-8 dealt with students’ opinion about the topics of the animated videos. Question 9-10 dealt with students’ opinion about the teacher’s role. Question 11-13 dealt with students’ opinion difficulty in speaking narrative Question 14-17 dealt with students’ response on teaching speaking narrative through animated videos. In analyzing the data, the writer presented the result of the observation checklist, score of the students’ speaking, and the result of questionnaires. The writer analyzed the whole phenomena of the teaching and learning activities which were in progress in a descriptive manner. The data of speaking result was analyzed based on the fact and the interpretation using FSI (Foreign Rating Procedure) which consists of pronunciation, grammar, vocabulary, fluency, and comprehension as can be seen in appendix 2.1 of the lesson plan, meanwhile, the questionnaires were described in words and sentences. RESULTS AND DISCUSSIONS In this chapter, the writer would like to answer the questions of the problem which have been stated in the first chapter. The questions of the problems are: 1. How is the implementation of teaching speaking narrative through animated fable videos? 2. How are the students’ speaking narrative after the implementation of animated fable videos? 3. How are the students’ responses in teaching speaking narrative text through fable videos? To answer those questions, the writer would like to describe the teaching learning process as the results of observation, to find out the result of students’ speaking narrative after the implementation of video, and to find out the students’ responses toward the implementation of video in teaching speaking narrative through animated fable videos. The Results of the Observation In this part, the writer describes the results of the observation in the implementation of video in teaching speaking narrative through animated fable videos. Before moving on playing the video, he distributed small sheets of the questions for the students to take a note. He told them that they just had to answer the question one up to six. As soon as he had this done, he explained to the students that the video would be without any sound on and they should guess how the story was. A few minutes the video had been watched, the teacher gave them a few minutes to work on the dictionary, to work in pairs to answer the questions from the video and wrote some key words on the board, such as pot, fly, and drop. Soon after this, the teacher asked them in turn how the story was,till the whole question were completed. What animal was it? Why was he flying? Where was the pot? What was he doing on the pot? How could he drink the water? What can you learn from story? 7. Please retell the story of the video? The Discussion of the Observation In teaching speaking text through animated fable video, there were several points to be discussed further. The points dealt with the teacher’s activity, the students’ activity, teaching and learning process, material used, and media used. The Teacher’s Activity During the implementation of teaching speaking narrative through animated fable videos, the writer observed that the teacher had already prepared the material before. This could be seen from those of three kinds of material dealing with speaking narrative. They were” The Thirsty Crow, “The Dove and The Ant”, and “The Foolish Fox”. The teacher introduced and showed the topic to the students in every meeting. He always introduced the topic at the beginning of the lesson and stimulated the students about the related material before beginning the class. The stimulation was by showing the image of the video in order that the students were curious to know what the story would be. To get the students more familiar with the regular and irregular verbs, he wrote some of them on the board so that they could easily repeat after him and understood well. Then, in teaching speaking narrative through animated fable video, the teacher only gave the example at the first meeting to the students, since it was the same steps to second and the third meeting. The way the teacher explained to the students was in a simple way and simple English, therefore, the students could easily caught and understood his English and explanation. Furthermore, in every part of meeting, the teacher always introduced new vocabularies to the students such as the vocabulary and verbs related to video and also asked and helped overcame the students’ difficulties in their speaking narrative. The Students’ Activity The activity of students was one of the parts in the observation about teaching speaking narrative through animated fable video. Here was to see how the students gave responses to the teacher’s explanation and the activeness on speaking narrative. They answered not only all of the teacher’s questions but understood the explanation as well. It could be seen from short questions given by the teacher and they could give correct answers and were able to present narrative story well from the video. It indicated that they actively followed the lesson. Even though the difficulties were mostly caused by the structure and lacking of vocabularythe teacher always gave feedback to the students, so that they could understand and knew what they had trouble with. Teaching and Learning Activity. The teaching and learning activity of teaching speaking narrative through animated fable videos consisted of three stages. They were pre- viewing activity, viewing activity, and post-viewing. In the teaching and learning activity used some techniques: active viewing, freeze faming, repetition, silent viewing and reproduction activity. First stage was pre-viewing activity, the teacher prepared the media which was suitable with the students’level in order to make the students easily understand the topic. The media used was a short video which only last three to four minutes as well as functioned to avoid students’ boredom. This way, the teacher believed that they were relevant media and could make the teaching learning process interesting. After selecting the media, the teacher, then, introduced the activity to the students. The introduction was in the form of asking the students’ prior knowledge and related information of the topic. The topic selected itself was often found in their text books such as similar topics of the animated fables,” Kaalu, the thirsty crow, the dove and the ant and the foolish fox” as it was mentioned above and was specially aimed the students to learn better in speaking narrative or to retell stories In the second stage after introducing the topics, the teaching learning process came to viewing activity. In this stage, the teacher paused and played the video for repetition in teaching words. Thismade the students got fully attention and be more familiar with the words. In addition, whilst viewing, the teacher and the students made a short discussion on the visualization about what the narrator said, what he was doing, and why he was doing that etc. The last stage was post-viewing in which the teacher asked the students’ difficulties and new vocabularies found in the visualization. He then tried to talk it over. After talking over students’ difficulties, the students were asked to present their speaking narrative in front of the class based on the theme of visualization they watched on that day and they were allowed to work with the friend for discussion. Material The material used in teaching speaking narrative through animated video was very relevant since narrative text is one of the competences that the students should accomplish, from junior high school to senior high school. Learning narrative through videos could also meet students’ interest and made thembe more actively engaged in the teaching and learning activities. Media The video used in the classroom media was good as it could be seen and heard clearly to the whole class. The students, therefore could easily catch the video scenes and they looked to enjoy it and paid more attention to the video. As long as watching the video, they were taking notes of what was being presented and just very few of them was occasionally out of their attention but soon got back to continue watching it. It could be concluded meant that teaching and learning English through video could give a great motivation to them. Result of the Students’ Speaking After the Implementation of Video In this part, the writer would discuss the result of students’ speaking after the implementation of animated fable video. The students’ speaking task was used to find out if implementation of animated videos could be good media in teaching speaking narrative. In this section, the writer analyzed their speaking skills by using FSI rubric by Oller. The things analyzed were pronunciation, grammar, vocabulary, fluency, and comprehension as in the tables below, and to get the final score is =result. FSI Speaking Assessment Proficiency Description 1 2 3 4 5 6 Pronunciation 0 1 2 2 3 4 Grammar 6 12 18 24 30 36 Vocabulary 4 8 12 16 20 24 Fluency 2 4 6 8 10 12 Comprehension 4 8 12 15 19 23 Total Score Conversion Score Assessment excellent 85-100 Good 70-85 Fair 60-70 Poor 50-59 Very poor 40-50 Pronunciation Grammar Vocabularies Fluency Comprehension Discussion of the Questionnaire From the data of the questionnaire, the writer found out that the students majority liked English and the implementation of the video as a media in English teaching learning activities. They agreed that it was an interesting media and understandable. Even so, some others said that they did not really like it. It happened because it was new for them and because of their lack of vocabularies so that they needed to work with the dictionary, asked their other friends or the teacher to find the right meaning of the difficult words. Thinking that speaking is the hardest thing to do, the students however said that learning through animated fable video had helped them find ideas to speak in narrative as well as help them remember the English vocabulary better. The teacher had also given them good motivation and support to be willing to ask freely anytime they had difficulties in speaking narrative. In summary, based on the results of observation, students’ speaking progress, and questionnaires, the writer concluded that teaching speaking narrative through animated videos was an effective way to help students improve their speaking narrative. CONLUSION AND SUGGESTION The last chapter of this study are the conclussion and suggestion. These both are very important either for the readers or the next researchers in order to find out easily and the brief results of this study. Conclussion The first conclussion is about the result of teaching speaking narrative through animated fable videos. The second one is the speaking task which concludes the result of students’ speaking narrative after the implementation of video. The last one is about the result of students’ responses towards teaching speaking through animated fable videos. The implementation of teaching speaking narrative through animated fable video In the implementation of teaching speaking narrative through animated fable video, there are three stages of video viewing. Those are pre-viewing activity, viewing activity, and post-viewing activity. In pre viewing activity, the teacher stimulates and motivates the students in order to name the topics. In viewing activity, the teacher plays the video several times then discusses the topic and the whole story of the video with the students. In post viewing activity, the teacher asks the students’ difficulties during and helps them find the solution. Afterwards for the last activity, the teacher asks the students to retell the story of the video. The students’ speaking narrative after the implementation of videos Having analyzed the students’ speaking narrative through animated videos from the first to the last meeting, the writer noticed that the students mostly have similarity in retelling their story because they have to retell the story from the same video they have watched together and the difference is with the quality of each component since in speaking ability involves pronunciation, grammar, vocabulary, fluency and comprehension, but dealing with the students’ speaking in retelling the story from the video, the students mostly shows good progess and get more familiar with the words in the narrative story from the video. The students’ responses towards teaching speaking narrative the animated fable videos Seen from the result of the questionnaire, it can be drawn into conclussion that the students like the implementation of teaching speaking narrative through animated fables video. They agree that the use of video in teaching speaking is very helpful in getting their ideas to speak and also the students agree to use videos as a media in teaching speaking. Suggestions In the findings of the research in teaching speaking narrative through animated fable videos, the writer realized that there should be revisions in many parts in the hope that it will become better results for the next research which can be done by the teachers or other researchers related to the implementation of video in teaching speaking narratives since videos can be applied into any English methodology needed. For Teachers Teachers play many important roles in teaching, learning process. They should always have an ability to carry out the right strategy in the classroom to help students understand and practice the learning materials easier. Besides that, Teachers are expected to always have ideas and creativities to enhance and to motivate the students to take part in the class activity. In this matter, rapid advance technology, like video, can help students more focus on the target language presented through the video. On the other hand, the use of video is able to meet the students’ level and interest, and to apply them into any kinds of activities to complete the four competences such as speaking, reading, writing, and listening. For Other Researchers As it has been stated that the implementation of video can be done in any kinds of activities. But here, it is not only the teachers but also the other researchers can do that. And if it is so, the writer suggests and hopes to the next researchers to follow up or have better revisions if they find unsatisfactory results of this research. For Students Students should be more confident and braver in speaking practise in order that they can share their ideas, opinion, and imagination in form of speaking, to avoid feeling scared or shy of having grammatical errors, less vocabulary and ideas while they are trying to speak English. To speak good English is to keep on practising the very basic things to take into speaking habits in any circumstances any where and any time and enlarge their lack of vocabulry to speak it by watching English videos and movie, reading English magazine, dialogue books or other sources of how to master English in which is now easy to access. REFERENCES REFERENCES Warschauer, M., & Healey, D. (1998). Computers and language learning: An overview. Language Teaching, 31, 57-71. Sherman, J. (2003). Using Authentic Video in the Language Classroom.Cambrigde: Cambridge University Press. Arthur, P. (1999). “Why use video?” A teacher’s perspective. The Internet TESL Journal.March 8, 2013, from http://www.tojet.net/articles/549.doc.html. Brown, and G. Yule. (1983). Teaching the spoken language. New York: Cambridge University Press. Chaney (1998) p. 13 “Teaching Speaking: Activities to Promote Speaking in a SecondLanguage “March 2, 2013, from http://iteslj.org/Techniques/KayiTeachingSpeaking.html Young (1985).vol 7 no 2 “young children's cognitive engagement during classroom book reading: differences according to book, text genre, and story,” March 7 2003 http://ecrp.uiuc.edu/v7n2/moschovaki.html Stephen Denning, The Springboard: How Storytelling Ignites Action in Knowledge-Era Organizations. Boston, London, Butterworth Heinemann, October 2000. Christine Canning-Wilson (2000), Practical Aspects of Using Video in the Foreign LanguageClassroom, march 9, 2013from http://iteslj.org/Articles/Canning-Video.html Elliott, Sheffield South CLC (Feb. 2011).Use of Video and Animation in the MFL Classroom Peter & Karen Viney(2004)Techniques for teaching with video Swain, (1985)ESL“We learn to speak by speaking,” BBC learning English Miguelbengoa| March 19th,( 2011) Teaching speaking: fluency or accuracy? http://www.youtube.com/watch?v=WPktMBW2k98,March 2, 2013, Kaalu, The thirsty crow http://www.youtube.com/watch?v=gFXgePGHrso, March 8, 2013, The ant and the dove http://www.youtube.com/watch?v=EjvmoNnsat8, March 8, 2013,The foolish fox http://aguswuryanto.wordpress.com/2011/09/13/rubrik-penilaian-pembelajaran-bahasa-inggris/ Altman, R. (1988). The video connection: Integrating video into language teaching. Boston, MA: Houghton Mifflin. Karen D. Wood & Josefina Tinajero(2002),”Using Pictures to Teach Content to Second LanguageLearners” http://www.amle.org/Publications/MiddleSchoolJournal/May2002 Long, Q. (2003).A study of teaching English listening and speaking through films.Media in Foreign Language Instruction, 3, 1-10. http://oxforddictionaries.com/definition/english/animation http://www.englishdirection.com/2011/03/kinds-of-narrative.html Rosen, (2005) http://recountext.blogspot.com/2011/04/narrative-texthtml http://en.wikipedia.org/wiki/Animation Fable http://www.taleswithmorals.com/